The relationship between different types of caries and periodontal disease severity in middle-aged and elderly people: findings from the 4th National Oral Health Survey of China - Li Xia Yu; Xing Wang; Xi Ping Feng; Bao Jun Tai; De Yu Hu; Bo Wang; Chun Xiao Wang; Shu Guo Zheng; Xue Nan Liu; Wen Sheng Rong; Wei Jian Wang; Yan Si; et al. (BMC, 2021)
Abstract Background The relationship between dental caries and periodontal disease is still controversial. The objective of this study was to explore the relationship between different types of caries and periodontal disease severity in middle-aged and elderly people in China. Methods The study population consisted of 4407 middle-aged and 4117 elderly subjects. Caries were divided into the following three types: type A, crown caries; type B, lesions involving both the crown and root, representing mixed-type caries; and type C, root caries. These three types together represent the overall caries situation, which we call type ABC. Caries were quantitated by decayed and filled teeth (DFT index). Periodontitis was evaluated by clinical attachment loss. Results Middle-aged people with periodontitis had a significant association with DFT type B (OR: 1.21, 95% CI 1.17-1.25) and type C (OR: 1.40, 95% CI 1.24-1.56). Elderly people with periodontitis had a significant association with DFT type C (OR: 1.28, 95% CI 1.21-1.35). Conclusions In China, caries types B/C were positively correlated with periodontitis in the middle-aged group, and only caries type C was positively correlated with periodontitis in the elderly group.